تقنين مقياس إستراتيجيات التعلم المنظم ذاتيا على تلاميذ الرابعة متوسط في البيئة الجزائرية - جعيجع, سميرة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2019)
اهتمت الدراسة الحالية بتقنين مقياس استراتيجيات التعلم المنظم ذاتيا للطفي عبد الباسط إبراهيم على طلبة السنة الرابعة المتوسط في البيئة الجزائرية وبالتحديد في ولاية المسيلة. ولهذا الغرض اتبعت الباحثة منهج طريقة الرائز على عينة اختيرت بطريقة عشوائية قوامها 183 تلميذ وتلميذة في مجتمع البحث الذي تكون من 579 تلميذ وتلميذة موزعين على أربع متوسطات في ولاية المسيلة. ومن اجل الإجابة على تساؤلات الدراسة، قامت الباحثة بحساب الخصائص السيكومترية (الصدق والثبات) للمقياس بعد تطبيقه على عينة الدراسة.وتم حساب الصدق بطريقة الاتساق الداخلي حيث كانت قيم معاملات الارتباط لكل بعد بالدرجة الكلية للمقياس كلها دالة احصائيا عند مستوى الدلالة 0.01 وتراوحت جميعها بين( 0.452 و0.839). وكانت معاملات الارتباط لفقرات كل بعد مع الدرجة الكلية للبعد دالة عند مستوى الدلالة 0.01 وتراوحت بين (0.31 و0.81). كما ان معاملات الارتباط لفقرات ابعاد المقياس بالدرجة الكلية للمقياس جاءت دالة احصائيا عند مستوى الدلالة (0.01و0.05) ماعدا الفقرة رقم (55) التي هي من الفقرات السالبة فقد جاءت غير دالة، وهذا يؤكد مدى التجانس وقوة الاتساق الداخلي للمقياس، وهو دليل على ان كل عبارات المقياس تقيس فعلا ما وضعت لقياسه. وتم حساب الثبات بطريقتين: الفا كرونباخ حيث جاءت جميع معاملات ألفا كرونباخ لأبعاد المقياس مرتفعة تراوحت بين (0.678 و0.742)، وللمقياس ككل 0.709 وهذا بمثابة مؤشر دال على ثبات المقياس. والطريقة الثانية هي التجزئة النصفية حيث بلغ معامل الارتباط بين نصفي المقياس 0.90 مما يدل على وجود ارتباط عالي بين النصفين، وهذا يدل على ثبات المقياس. وللإجابة على التساؤل الثاني: تم اشتقاق معايير محلية للاختبار وذلك بالاعتماد على المعيار الميئيني باعتباره من أكثر الطرق استخداما في تفسير درجات الاختبار والمقاييس النفسية، وبهذا تكون الباحثة قد تأكدت من صلاحية المقياس للتطبيق في البيئة المحلية This study focus on the standardization ofLofiAbd –Elbaset Ibrahim’s self-regulated learning strategies scale applied on fourth year AM Algerian pupils precisely in M’sila district. Therefore, the researcher followed the test method on183 pupils sample randomly selected from the study population of 579 pupils spread over four medium schools in M’sila. To answer research questions, the researcher proceed to measure the psychometrical properties (reliability and validity) of the scale after applying it on the research sample. The validity measured by internal consistency method, where correlation coefficients values for each dimension in the total degree of the scaleare all statistically significant at the level of significance 0.01, and ranged between (0.452 and 0.839). Moreover, the correlation coefficients of each dimension paragraphswith the full grade of that dimension was significant at the level of significance 0.01, and ranged between (0.31 and 0.81).The correlation coefficients of the dimensions paragraphs of the scale in the total degree of the scale were statistically significant at the level of significance (0.01 and 0.05) except paragraph (55), which is negative paragraphs were not significant.This confirms the degree of homogeneity and the strength of the internal consistency of the scale, and is proof that all the terms of the scale actually measure what they are designed to measure. Reliability was measured in two ways: Alpha Cronbach, where all the coefficients of Alpha Cronbach of the scale dimensions were high ranging between (0.678 and 0.742), and to the scale as a whole were around 0.709. This is a sign of the reliability of the scale. The second is the split half method, where the correlation coefficient between the two halves of the scale was 0.90, which indicates a high correlation between the two halves, which indicates the reliability of the scale. To answer the second question: local norm for the test were derived by relying on the percentile norms as one of the most used methods in the interpretation of test grades and psychological standards, and thus the researcher has confirmed the validity of the scale for application in the local environment.
Keywords: التقنين- مقياس إستراتيجيات التعلم المنظم ذاتيا- تلاميذ الرابعة متوسط.